Pengabdian Masyarakat Bagi Pokdarwis Krenomata RW 3 Kelurahan Kemirirejo, Kota Magelang Untuk Merintis Kampung Wisata Edukasi - Anissa Hakim Purwantini; Farida Farida (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
Kampung Rukun Warga (RW) 03 Kelurahan Kemirirejo, Central Magelang Regency, Magelang City has various potentials to be developed as a pilot educational tourism village. The enthusiasm of the community can also be seen with the formation of a tourism awareness group (pokdarwis). However, the management of Pokdarwis Krenomata in RW 03 still does not understand the roles and functions as well as how the strategies and next development steps are to realize an Educational Tourism Village. Therefore, training and mentoring are needed to optimize the role and function of Pokdarwis in order to formulate the right strategy for realizing a tourist village. The purpose of this service is to provide an understanding of the role and function of pokdarwis, mentoring the concept of a tourism village, and business management consisting of marketing strategies, financial records and simple bookkeeping, and charms. This service provides skills and knowledge to pokdarwis administrators and members in pioneering educational tourism villages. The formation of this educational tourism village is expected to encourage the economic independence of the urban community, especially the City of Magelang.